Strategies of expressing written apologies in the online newspaper - Cipto Wardoyo (Universitas Islam Negeri Palangka Raya, Indonesia, 2014)
Expressing apology is a universal activity although people have different strategies or ways to express the apology based on the culture, situation, and context. An apology has played a vital role in verbal politeness; it is certainly impolite when someone does not express an apology when he or she has commited an offence to the others. Apologies in the Pragmatic study is classified under speech act theory. An apology based on Searle (1969) is classified as expressive speech acts because it expresses speaker